Analisis Mitigasi Bencana terhadap Kondisi Sosial Budaya di Gorontalo - Rijal, Ahmad Syamsu; Matalapu, Irawan; Jaya, Risman; Maulana, Karina Meiyanti (UNIVERSITAS NEGERI MAKASSAR, 2021)
The purpose of this study was to analyze the socio-cultural conditions related to disaster mitigation in Gorontalo. The method used in this research is a survey with data collection techniques. The data analysis technique used is SWOT (strengths, weaknesses, opportunities, and threats) by looking at the socio-cultural conditions of the people of Gorontalo related to disaster mitigation in Gorontalo. The results of the study show that most information on disaster mitigation is known from school as well as from various media sources. Community, students, and teachers often experience disaster mitigation such as earthquakes, floods, and landslides, so it is necessary to have an evacuation place that is ready to be occupied. Lack of public awareness to join organizations on disaster mitigation means that most people do not know about preparedness in facing disasters that will occur. Disaster mitigation practice activities taught in schools are a solution to teach students to understand more about how to save themselves from disasters and not easily panic and fear.